Representações da infância ultrajada e da criança-herói: uma leitura de Charles Dickens e Jorge Amado - Diniz, Luis de Melo (2013)
The aim of this thesis is to conduct a comparative study between the works Oliver Twist (1837) of the English novelist Charles Dickens, and Capitães da Areia (1937), a narrative of the Brazilian writer Jorge Amado, in which we highlight the representations of the child - more specifically that one in state of neglecting and poverty in urban middles of Europe and Brazil, as well as its role as hero in the environment of the two novels. Even considering the differences between these two narratives, in relation to the historical and social contexts and to the writing models the first one coming from the English universe in the early nineteenth century, affiliated to the British realist aesthetics, and the second developed in the northeastern of Brazil in the beginning of the twentieth century, which is clearly based on the tendency of the 30 s modernist novel. These two narratives are approached through a common theme: the abandonment and violence against the helpless and abandoned child left to its own destiny. In these two novels child is highlighted as central character, which justify our attempt of approach between the two authors. In this sense we believe we have succeeded in confirming our hypothesis that both narrators while revealing the contradictions of their societies, English Victorian and Brazilian of 30 s, try (through their literary texts) to point aesthetic routes to denounce the existing contradictions in their realities.